EVALUATIVE RESEARCH PARADIGMS IN EDUCATIONAL PROGRAMS - Flores Barboza, José (2014)
The article focuses on the confrontation /comparison? between the naturalistic and the experimental paradigms to evaluate educational programs. It examines the theoretical framework of each paradigm and the proposed methodology to pursue an evaluation. Finally, the article addresses the possibility of a reconciliation between both paradigms.